Optopharmacological tools for restoring visual function in degenerative retinal diseases - Tochitsky, Ivan (Curr Opin Neurobiol, 2015)
Retinitis pigmentosa (RP) and age-related macular degeneration (AMD) are progressive retinal diseases that result from the death of rod and cone photoreceptors, ultimately leading to blindness. The only currently approved vision restoration treatment employs an implanted retinal ‘chip’ as a prosthetic device to electrically stimulate retinal neurons that survive after the photoreceptors are gone, thereby restoring light-driven neural signaling to the brain. An alternative strategy has been proposed, which would utilize optogenetic or opto-pharmacological tools to enable direct optical stimulation of surviving retinal neurons. Here, we review the latest studies evaluating the feasibility of these molecular tools as potential therapeutics for restoring visual function in human blinding disease.